Caracterización de la eficiencia energética en los sistemas de refrigeración aplicados en el área automotriz. Seleccionar intercambiadores de calor coaxiales para incrementar el coeficiente de desempeño en los sistemas de refrigeración - Cuaical, Bolívar Alejandro Angulo (2017)
The present research was carried out with the purpose of characterizing experimentally the performance coefficient of automotive air conditioning systems and to determine the effect of three heat exchangers of straight geometry and cross flow in the refrigeration cycle, being able to determine experimentally a geometry Suitable to increase the performance coefficient by interfering the high pressure line between the condenser and the expansion valve as well as the low pressure line between the evaporator and the compressor at 1 750 rpm and 1 805 rpm using R-134a refrigerant, Obtaining by means of statistical regressions a correlation between the temperature variations in the low pressure line of 86.86% and in the line of high pressure of 95.17% as a function of the volumes of the exchangers analyzed.